2003
DOI: 10.1038/sj.bjp.0705414
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between peroxisome proliferator‐activated receptors (PPARα and PPARγ) and endothelium‐dependent relaxation in streptozotocin‐induced diabetic rats

Abstract: 1 The aim of the present study was to investigate the causal relationship between peroxisome proliferator-activated receptor (PPAR) and endothelium-dependent relaxation in streptozotocin (STZ)-induced diabetic rats. 2 Acetylcholine (ACh)-induced endothelium-dependent relaxation was significantly weaker in diabetic rats than in age-matched controls. The decreased relaxation in diabetes was improved by the chronic administration of bezafibrate (30 mg kg À1 , p.o., 4 weeks). 3 The expressions of the mRNAs for PPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 68 publications
3
35
0
Order By: Relevance
“…Furthermore, we found that chronic administration of a relatively low dose of bezafibrate, which was insufficient to alter the levels of plasma lipids (including total cholesterol, LDL cholesterol, high density lipoprotein (HDL) cholesterol, and triglyceride), exerted an improvement effect on the endothelial dysfunction seen in the aorta in rats with established STZ-induced diabetes. This effect of bezafibrate may result from a reduction in the NAD(P)H oxidase p22phox subunit through an inhibitory effect on ET-1 synthesis (Kanie et al, 2003).…”
Section: Mechanisms Underlying Impaired Endothelial Function In Diabementioning
confidence: 99%
“…Furthermore, we found that chronic administration of a relatively low dose of bezafibrate, which was insufficient to alter the levels of plasma lipids (including total cholesterol, LDL cholesterol, high density lipoprotein (HDL) cholesterol, and triglyceride), exerted an improvement effect on the endothelial dysfunction seen in the aorta in rats with established STZ-induced diabetes. This effect of bezafibrate may result from a reduction in the NAD(P)H oxidase p22phox subunit through an inhibitory effect on ET-1 synthesis (Kanie et al, 2003).…”
Section: Mechanisms Underlying Impaired Endothelial Function In Diabementioning
confidence: 99%
“…In such animals, we previously reported that: (1) the plasma ET-1 level is increased and that this increase may be due to an overexpression of the mRNA for prepro-ET-1 (Makino and Kamata, 1998;Makino et al, 2001), (2) the overproduction of ET-1 seen in STZ-induced diabetes results from the hyperglycemia, not from any increase in either LDL cholesterol or triglyceride (Makino and Kamata, 2000), (3) the expression of the mRNA for p22phox is increased in STZinduced diabetes, an increase that is completely preventable by the chronic administration of J-104132 (a potent, orally active, mixed antagonist of ETA and ETB receptors) (Kanie and Kamata, 2002), and (4) short-term or prolonged treatment with ET-1 impairs endothelial function in the aorta both in nondiabetic rats Matsumoto et al, 2007d) and in rats with established STZ-induced diabetes . Moreover, we have demonstrated that chronic administration of the PPARα agonist bezafibrate to established STZ-induced diabetic rats normalizes both the mRNA for prepro-ET-1 and the plasma concentration of ET-1, while improving endothelium-dependent relaxation (Kanie et al, 2003). In that paper, we also demonstrated that the expressions of the mRNAs for PPARα and PPARγ were downregulated in aortic segments from STZ-induced diabetic rats (Kanie et al, 2003).…”
Section: Pparγ Agonists and The Endothelin Systemmentioning
confidence: 50%
“…Moreover, we have demonstrated that chronic administration of the PPARα agonist bezafibrate to established STZ-induced diabetic rats normalizes both the mRNA for prepro-ET-1 and the plasma concentration of ET-1, while improving endothelium-dependent relaxation (Kanie et al, 2003). In that paper, we also demonstrated that the expressions of the mRNAs for PPARα and PPARγ were downregulated in aortic segments from STZ-induced diabetic rats (Kanie et al, 2003). In the recent paper referred to above, we found that the elevated plasma ET-1 level seen in such established STZinduced diabetic rats can be largely suppressed by chronic treatment with pioglitazone, and that the increased expression of aortic c-Jun (an AP-1 component) seen in such rats is greatly reduced by the pioglitazone treatment (Matsumoto et al, 2007d).…”
Section: Pparγ Agonists and The Endothelin Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperglycemia in both type 1 and type 2 diabetes mostly results from the loss of β-cell mass that would lead to considerable morbidity in the globe population. Lately, an option and promising approach in expansion is to stimulate the regeneration of endogenous β-cells to replace the deficit in β-cell mass in diabetic patients [45][46][47][48]. Peroxisome proliferator-activated receptor a (PPARα and PPARγ), which is activated by specific agonists as fatty acid and fibrates forms heterodimers associated with PPAR response elements in the promoter region of target genes and retinoid X receptor [49].…”
Section: Dissuasionmentioning
confidence: 99%